A critical review on strategies for improving efficiency of BaTiO3-based photocatalysts for wastewater treatment. (15th July 2021) - Ray, Schindra Kumar; Cho, Jinwoo; Hur, Jin
Abstract: Barium titanate (BaTiO3 ) photocatalysts with perovskite structures are promising candidates for the effective removal of hazardous organic pollutants from water/wastewater owing to several advantages, including low cost, non-toxicity, high stability, environmental friendliness, favorable band positions, high oxygen vacancies, multiple crystal phases, rapid migration of charge carriers at the surface, band bending, spontaneous polarization, and easy tailoring of the sizes and morphologies. However, this high dielectric/ferroelectric material is only active in UV light (band gap: 3.2 eV), which reduces the photocatalytic degradation performance. To make barium titanate more suitable for photocatalysis, the surfaces of the powders can be modified to broaden the absorption band. In this paper, various strategies for improving photocatalysis of barium titanate for removing organic pollutants (mostly dyes and drugs) from water/wastewater are critically reviewed. They include modifying the sizes and morphologies of the particles by varying the reaction times and synthesis temperatures, doping with metals/non-metals, loading with noble metal NPs (Ag and Au), and fabrication of heterojunction photocatalysts (conventional type II and Z-scheme). The current challenges and possible future directions of BaTiO3 -based materials are also discussed. This comprehensive review is expected to advance the design of highly efficient BaTiO3 -based materials for photocatalytic applications in water/wastewater treatment. Graphical abstract: Image 1 Highlights: BaTiO3 -based photocatalysts is first reviewed for wastewater treatment. Strategies to enhance charge carrier separation are overviewed for photolysis. Morphology/size-tuned, doped, plasmonic, and composite photocatalysts are explored. Insight into limitations, current challenges, and future perspectives are provided.